2006
DOI: 10.4049/jimmunol.176.11.6862
|View full text |Cite
|
Sign up to set email alerts
|

Precursor B Cell Receptor Signaling Activity Can Be Uncoupled from Surface Expression

Abstract: Signals from the precursor BCR (preBCR) cause proliferation and differentiation of progenitor (pro-) B cells into pre-B cells. Given the very low amounts of surface preBCRs and the demonstrated cell autonomy of preBCR signaling, we examined the possible occurrence of preBCR signal propagation from intracellular membranes such as the endoplasmic reticulum (ER) and the trans-Golgi network (TGN) in transformed and primary pro-B cells. PreBCRs composed of normal Ig μ or truncated Dμ heavy chains (HCs) were redirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Furthermore, studies using Ig heavy chains that are targeted to the endoplasmatic reticulum (ER) or the Golgi apparatus revealed that the signal initiation of the pre‐BCR may occur in parts from the trans‐Golgi network rather than the ER. This Golgi‐derived signal was sufficient to induce proliferation and upregulation of differentiation markers CD2 and CD22 and may explain the strong signaling effects of the pre‐BCR despite its low surface expression .…”
Section: Pre‐bcr Signaling and Function In Normal B‐cell Progenitorsmentioning
confidence: 99%
“…Furthermore, studies using Ig heavy chains that are targeted to the endoplasmatic reticulum (ER) or the Golgi apparatus revealed that the signal initiation of the pre‐BCR may occur in parts from the trans‐Golgi network rather than the ER. This Golgi‐derived signal was sufficient to induce proliferation and upregulation of differentiation markers CD2 and CD22 and may explain the strong signaling effects of the pre‐BCR despite its low surface expression .…”
Section: Pre‐bcr Signaling and Function In Normal B‐cell Progenitorsmentioning
confidence: 99%
“…In pre-B cells, the pre-B receptor acts from an intracellular location to generate most, if not all, signals that promote B cell differentiation (31). Similarly, intracellular IgM may be competent for signaling because the BCR assembles and associates with Ig␣ and Ig␤ in a post-endoplasmic reticulum (ER) compartment (32).…”
Section: Vh56r؉v 38c Receptors Are Enriched In Marginal Zone (Mz) B Cmentioning
confidence: 99%
“…The time frame in which this mechanism operates is unknown, as is the compartment from which the signal is delivered. It is possible that the μ H chain‐mediated feedback signal that results in H chain allelic exclusion does not require surface expression, since μ H chains alone (in the absence of λ 5) can induce signalling, albeit at a low level, from the trans‐Golgi network [59]. Furthermore, it is possible that the signal for H chain allelic exclusion also induces cellular transition from the pre‐BI to the pre‐BII stage, since a functional H chain is sufficient for this process.…”
Section: Discussionmentioning
confidence: 99%